Evolução e Ontologia Moral - Eduardo César Campos Coelho (2018)
This dissertation analyzes the consequences that an evolutionary genealogy of our moral psychology can bring to traditional philosophical questions about the nature of moral values and how we can know them. In this sense, the inquiry that guides this dissertation has a conditional nature: if the evolutionary process has influenced the genesis of our moral beliefs and attitudes, then what are the consequences, if any, for the metaphysics and epistemology of moral values? Specifically, three contemporary philosophers – Michael Ruse, Sharon Street, and Richard Joyce – argue, each in their own way, in favor of some skeptical thesis for the possibility of knowledge or the existence of objective moral values. In response to them, other philosophers – David Copp, Erick Wielenberg, David Enoch, William FitzPatrick, Erick Shafer-Landau, among others – argue that nothing in the evolutionary genesis justifies such consequences. The focus of the work will be to analyze this controversy. However, before that, two propaedeutic topics are important to motivate the debate. First, it is important to understand the general line of what motivates and what is the nature of the positions that espouse an objective nature for morality – specifically, called moral realism in contemporary English-language philosophy. Second, it is necessary to present, albeit briefly, the empirical arguments in favor of the thesis that moral psychology is the product of the evolutionary process. In this way, the first chapter of the paper will address moral realism and the reasons for defending it. The second chapter will present the scientific hypothesis of the evolutionary origin of morality. The third chapter will discuss the skeptical arguments of Michael Ruse, Sharon Street and Richard Joyce. Finally, the fourth chapter will examine the counterarguments to evolutionist skepticism about moral objectivity.